South African money market volatility, asymmetry and retail interest pass-through - Fadiran, Gideon Oluwatobi (Rhodes University, Faculty of Commerce, Department of Economics, 2011)
The purpose of this paper is to examine the interest rate transmission mechanism for South Africa as an emerging economy in a pre-repo and repo system. It explains how the money market rate is transmitted to the retail interest rates both in the long-run and short-run and tests the symmetric and asymmetric interest rate pass-through using the Scholnick (1996) ECM and the Wang and Lee (2009) ECM-EGARCH (1, 1)-M methodology. This permitted the examination of the impact of interest rate volatility, along with the leverage effect. An incomplete pass-through is found in the short-run. From the entire sample period, a symmetric adjustment is found in the deposit rate, which had upward rigidity adjustment, while an asymmetric adjustment is found in the lending rate, with a downward rigidity adjustment. All the adjustments supported the collusive pricing arrangements. According to the conditional variance estimation of the ECM-EGARCH (1, 1), negative volatility impact and leverage effect are present and influential only in the deposit interest rate adjustment process in South Africa.
Keywords: Money market -- South Africa; Interest rates -- South Africa; Monetary policy -- South Africa; Econometric models; Banks and banking -- South Africa